Employee engagement in continuous improvement of processes = Zaangażowanie pracowników w ciągłe doskonalenie procesów - Brajer-Marczak, Renata (Zielona Góra: Faculty of Economics and Management Press)
The article, which is supposed to present the essence of the problems related to building employee engagement in continuous improvement of processes, highlights the existing possibilities of its extraction and sustaining. The paper has pointed out that the subject matter associated with building employee engagement in improvement of processes is cognitively interesting, but also useful in practice, especially that, as indicated in the first part of this study, without any knowledge and skills associated with improvement of processes it is currently difficult to compete in a variable market environment.
Keywords: proces; doskonalenie procesów; zaangażowanie pracowników; process; improvement of process; continuous improvement of processes; employee engagement